The effect of compensation and religiosity on managers’ CSR decision - Poppy Dian Indira Kusuma; Wiwiek Rabiatul Adawiyah; Bambang Agus Pramuka; Zahrotush Sholikhah (Jurnal Keuangan dan Perbankan, 2020)
This study aims to examine the relationship between compensation schemes and religiosity and managers’ investment decisions in CSR. We argue that compensation scheme and managers’ level of religiosity associate with managers’ choice whether to invest in value-increasing or value-decreasing CSR. Data were collected through a laboratory experiment which involved 100 participants. The Chi-square test results show that managers who work under a performance-based compensation tend to choose a value-increasing CSR. Meanwhile, managers who work under nonperformance-based compensation tend to choose a value-decreasing CSR. However, this study failed to prove the relationship between manager’s religiosity level and CSR investment decision made by managers. A small variance of our participants’ religiosity level may lead to this finding. This research contributes to the CSR and behavioral finance literature by providing an understanding of how compensation and religiosity can direct managers’ investment decisions on CSR. Our results imply the importance of designing an appropriate compensation scheme in an organization in order to direct managers to make an optimal CSR decision.JEL Classification: M48, M12, M14 DOI: https://doi.org/10.26905/jkdp.v24i3.4063